Model Implementation Numbered Head Together On The Material Of Straight-Line Equations Through One Point Class Viii - Nafsiah, Nur Rosatin; Hadiyanti, Yosefin R.; Tandililing, Pitriana; Panjaitan, Agnes Teresa; Ruamba, Marthinus Y. (JUPE : Jurnal Pendidikan Mandala, 2025)
This research is a descriptive research using a qualitative research approach. The subjects of this research were 26 students of class VIII A SMP Al Ihsan Yapis Kotaraja. The selection of research subjects used the purposive sampling techniques. The research instruments used were teacher observation sheets, student observation sheets, and individual tests. The purpose of this research is to describe the application of the Numbered Head Together (NHT) learning model to the straight line equation material through one point in class VIII A SMP Al Ihsan Yapis Kotaraja. Based on the results of the analysis and discussion of the learning process by applying the Numbered Head Together (NHT) learning model, it went well. This is evidenced by the results of the teachers observations obtained the category of very good, the activeness of students obtained the high category, and the results of individual tests can help students to understand the material of straight line equations through one point.